Housing for bottom 50% income group in Malaysia: Housing satisfaction among elderly and disabled people - Shuid, Syafiee (2015)
The study focus on housing satisfaction among the low and middle low income elderly and disabled people living in public and private housing in Malaysia. It was based on Housing study for bottom 50% income group in Malaysia conducted by Economic Planning Unit (EPU) and United Nations Development Programmes (UNDP) in 2014. Generally, elderly and disabled also shared similar type of houses with normal person. The paper will highlight the issues faced by the elderly and disabled persons based on the interviews and survey conducted in selected communities. Among the issues including allocation of housing units, size of the unit, health services, public transportation and activities for the elderly and disabled people in the community. The recommendations including that Universal Design be used and a 1Malaysia Clinic be included in all future affordable and low cost housing to enable accessibility for the elderly and disabled. Where renovations are being made in existing units they should also follow Universal Design principles. It is further recommended that public transportation be made disabled accessible as per the International Best Practices, and including the training and certification of taxi drivers.